UNGKAPAN RUPA PAKAIAN PENGANTIN PEREMPUAN DITINJAU DARI BENTUK, MOTIF, DAN WARNA DI NAGARI MANGGOPOH KECAMATAN LUBUK BASUNG KABUPATEN AGAM - INES KASRIANTI, Dra. Zubaidah, M.Pd., Drs. Yusron Wikarya, M.Pd. (Serupa The Journal of Art Education, 2016)
This study aimed to describe the shape of bride clothing accessories, motif used, and color variations found on the clothes of the bride to be more known to the local community, national, and global. The research method using qualitative research with descriptive approach. The results showed that women in the bridal wear in nagari manggopoh lubuk basung subdistrict agam regency consists of several equipments as baju kuruang basiba, tongkah, saruang balapak, suntiang gadang, gelang gadang, kaluang pinyaram, kaluang rumah gadang, kaluang heart shaped, earring/subang payuang tajun and subang sisiak ikan, lacha (decoration on the forehead), and veil (shawl). The motifs on the bride clothes come from the shape of plants/flora and animals/fauna consisting of kaluak paku, bungo rose, sidingin leaf (cocor bebek) and the sowing of small jasmine flower motif (supporting motif). The bride clothing colors have variation as red, yellow, pink, and blue. But the dominant color is red which symbolizes courage, heroism and endurance and symbolizes the agam regency/luhak agam.Keywords: form, motif, bride clothing color